2021
DOI: 10.1111/febs.16050
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between SUMOylation and phosphorylation of PKCδ facilitates oxidative stress‐induced apoptosis

Abstract: Although the increase in the number of identified posttranslational modifications (PTMs) has substantially improved our knowledge about substrate site specificity of single PTMs, the fact that different types of PTMs can crosstalk and act in concert to exert important regulatory mechanisms for protein function has not gained much attention. Here, we show that protein kinase Cδ (PKCδ) is SUMOylated at lysine 473 in its C‐terminal catalytic domain, and the SUMOylation increases PKCδ stability by repressing its u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 86 publications
(123 reference statements)
0
6
0
Order By: Relevance
“…ESD4 maintains SnRK2.6 in a low SUMOylation level, which may inhibit the interaction of SnRK2.6 with other kinases to decrease its phosphorylation; alternatively, the deSUMOylation of SnRK2.6 may affect its ubiquitination level which promotes its degradation mediated by 26S proteasome. Consistent with this notion, in mammalian cells, the SUMOylation and phosphorylation of protein kinase Cδ (PKCδ) act in concert to enhance the ability of this kinase to mediate the oxidative damage to cells (Gao et al, 2021). Inhibition of PKCδ phosphorylation decreased its affinity for the SUMO conjugating enzyme (UBC9) and/or SUMO ligase (PIAS2).…”
Section: Discussionmentioning
confidence: 95%
“…ESD4 maintains SnRK2.6 in a low SUMOylation level, which may inhibit the interaction of SnRK2.6 with other kinases to decrease its phosphorylation; alternatively, the deSUMOylation of SnRK2.6 may affect its ubiquitination level which promotes its degradation mediated by 26S proteasome. Consistent with this notion, in mammalian cells, the SUMOylation and phosphorylation of protein kinase Cδ (PKCδ) act in concert to enhance the ability of this kinase to mediate the oxidative damage to cells (Gao et al, 2021). Inhibition of PKCδ phosphorylation decreased its affinity for the SUMO conjugating enzyme (UBC9) and/or SUMO ligase (PIAS2).…”
Section: Discussionmentioning
confidence: 95%
“…SUMOylation of hyperphosphorylated tau at K340 inhibits its ubiquitylation and the subsequent proteasome-dependent degradation ( 39 ). Gao et al showed that PKCδ was SUMOylated at lysine 473, and the SUMOylation increased PKCδ stability by repressing its ubiquitination ( 40 ). Besides, SUMOylation induces conformational changes in proteins and thereby regulates protein functions ( 41 43 ).…”
Section: Process Of Protein Sumoylationmentioning
confidence: 99%
“…Based on the findings of Siman Gao and colleagues [6], a rather complex picture emerges as to how post‐translational modification of PKCδ regulates apoptosis (Fig. 1).…”
Section: Molecular and Biochemical Analysis Of Post‐translational Mod...mentioning
confidence: 99%
“…The interesting findings of Gao and colleagues [6] raise some intriguing questions for further investigation. Firstly, it would be useful to determine whether hydrogen peroxide does indeed mediate a SUMO and phosphorylation‐dependent cleavage of PKCδ.…”
Section: Molecular and Biochemical Analysis Of Post‐translational Mod...mentioning
confidence: 99%
See 1 more Smart Citation